STRUKTUR KOMUNITAS MANGROVE DI PULAU JEMAJA, KABUPATEN KEPULAUAN ANAMBAS, DAN PULAU LIRAN, KABUPATEN MALUKU BARAT DAYA - Fuady, Irfan; Pribadi, Rudhi; Nirwani, Nirwani (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangrove Vegetation occupy the area between land and sea that have environmental conditions differ from one another. The purpose of this study is to know about the structure and composition of mangrove vegetation in Jemaja Island, Kepulauan Anambas Regency, Riau Islands Province, and Liran Island, South-East Moluccas Regency, Moluccas Province. Vegetation data taking based on purposive sampling method and every transect made sampling plot. Each tree (plot 10 m x 10 m) and sapling (subplot 5 m x 5 m) identified and measured on diameter at breast height (± 1.3 m). Seedling calculated the amount of each species and the percentage of cover on subplot 1 m x 1 m. The result of research in Jemaja Island was found 17 mangrove species. Tree mangrove in Jemaja Island have the range of density 375 ind/ha – 950 ind/ha were dominated by Rhizophora apiculata (Importance Index 89,73% - 123,42%). The result of research in Liran Island was found 19 mangrove species. Tree mangrove in Liran Island have the range of density 500 ind/ha – 566 ind/ha were dominated by Sonneratia alba with range of Importance Index 135,90% - 160,32%. The Index of Diversity (H’) and Eveness (J’) of mangrove vegetation in Jemaja Island, District of Anambas Islands and Liran Island, District of South-East Moluccas, were in low category.